Towards the Antiviral Agents and Nanotechnology-Enabled Approaches Against Parvovirus B19 - Hu, Xi; Jia, Chen; Wu, Jianyong; Zhang, Jian; Jiang, Zhijie; Ma, Kuifen (Frontiers in Cellular and Infection Microbiology, 2022)
Parvovirus B19 (B19V) as a human pathogenic virus, would cause a wide range of clinical manifestations. Besides the supportive and symptomatic treatments, the only FDA-approved antiviral drug for the treatment of B19V is intravenous immunoglobulins, which however, have limited efficacy and high cost. By far, there are still no virus-specific therapeutics clinically available to treat B19V infection. Therefore, exploiting the potential targets with a deep understanding of the life cycle of B19V, are pivotal to the development of B19V-tailored effective antiviral approaches. This review will introduce antiviral agents via blocking viral invasion, inhibiting the enzymes or regulatory proteins involved in DNA synthesis, and so on. Moreover, nanotechnology-enabled approaches against B19V will also be outlined and discussed through a multidisciplinary perspective involving virology, nanotechnology, medicine, pharmaceutics, chemistry, materials science, and other fields. Lastly, the prospects of the antiviral agents and nanosystems in terms of fabrication, clinical translation and potential breakthroughs will be briefly discussed.